Promiscuous Media : Film and Visual Culture in Imperial Japan, 1926-1945 - Hori, Hikari (Book collections on Project MUSE., 2017)
The early Showa Era (1926-45), which roughly coincides with the Nazi years (1920-45) and Mussolini's 'venti anni' (1921-43), is generally assumed to be a dogmatically and fanatically nationalist period, and due this putative monomania is often seen as a straightforward subject to study. To the contrary, this text reveals a very different picture of the Japanese popular media of this time period.